The Importance of Lymphovascular Invasion in Uterine Adenosarcomas: Analysis of Clinical, Prognostic, and Treatment Outcomes. Issue 7 (September 2018) - Nathenson, Michael J.; Conley, Anthony P.; Lin, Heather; Fleming, Nicole; Lazar, Alexander; Wang, Wei-Lien; Ravi, Vinod
Abstract : Objective: This retrospective study examined the clinicopathologic features of adenosarcoma patients to determine potential prognostic factors and retrospectively evaluated overall survival (OS), disease-free survival (DFS), and local recurrence-free survival (LRFS) after primary treatment of adenosarcoma including surgery, radiation, and chemotherapy. Methods: One hundred sixty-five patients with adenosarcoma were identified from the MD Anderson Cancer Center tumor registry between 1982 and 2014. Clinical data were collected retrospectively. Pathologic characteristics were examined by sarcoma pathologists. We used the Kaplan-Meier method to estimate OS, DFS, and LRFS. The log-rank test was performed to test the difference in survival between groups. Multivariate regression analyses of survival data were conducted using the Cox proportional hazards model. Results: Median OS and DFS for all patients were 8.5 and 4.7 years, respectively. Pathologic characteristics that influence OS and DFS were sarcomatous overgrowth (SO), myometrial invasion (MI), lymphovascular invasion (LVI), tumor size, number of mitosis, estrogen receptor, progesterone receptor, International Federation of Gynecology and Obstetrics (FIGO) stage, age, and resection status. Median OS for adenosarcoma patients with SO was 5.2 versus 14.5 years for patients without SO ( P < 0.0001). Median OS for adenosarcoma patients with MI was 5.8 years versus not reached for patients without MI ( P = 0.0005). Median OS for adenosarcoma patients with LVI was 1.0 versus 8.9 years for patients without LVI ( P = 0.0021). On Cox analysis for OS and DFS and LRFS, only SO, MI, LVI, age, resection status, and FIGO stage remained significant. There was no difference in OS or LRFS for adjuvant radiation versus no adjuvant radiation ( P = 0.17, P = 0.076). Conclusions: This study highlights the importance of LVI as a prognostic factor and confirms the prognostic significance of SO, MI, age, resection status, and FIGO stage for adenosarcoma. Furthermore, this study suggests that there is no additional benefit to adjuvant radiation. The standard-of-care treatment for adenosarcoma should remain total abdominal hysterectomy bilateral salpingo-oophorectomy +/− lymphadenectomy and no adjuvant radiation. Abstract : Supplemental digital content is available in the text.